2017
DOI: 10.1001/jamaophthalmol.2017.1153
|View full text |Cite
|
Sign up to set email alerts
|

Geographic Information Systems Mapping of Diabetic Retinopathy in an Ocular Telemedicine Network

Abstract: IMPORTANCE Minimal information exists on the use of geographic information systems mapping for visualizing access barriers to eye care for patients with diabetes.OBJECTIVE To use geographic information systems mapping techniques to visualize (1) the locations of patients participating in the North Carolina Diabetic Retinopathy Telemedicine Network, (2) the locations of primary care clinicians and ophthalmologists across the state, and (3) the travel times associated with traveling to the 5 primary care clinics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…We were unable to assess clinician referral rates in this study, but previous studies indicate that eye care referrals among patients with diabetes are suboptimal (4). Telemedicine using nonmydriatic fundus cameras has emerged as a viable and effective DR screening option (15)(16)(17). These photos can be taken by health care personnel in primary care settings and then transmitted to reading centers for evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…We were unable to assess clinician referral rates in this study, but previous studies indicate that eye care referrals among patients with diabetes are suboptimal (4). Telemedicine using nonmydriatic fundus cameras has emerged as a viable and effective DR screening option (15)(16)(17). These photos can be taken by health care personnel in primary care settings and then transmitted to reading centers for evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The North Carolina Diabetic Retinopathy Telemedicine Network (NCDRTN) is an innovative screening program developed to address the growing burden of DR in rural and underserved areas in the state. From 2014 to 2015, a total of 1,787 patients with diabetes in 5 Area Health Education Center primary care clinics received retinal screening photographs with remote expert interpretation to determine the presence and severity of DR [34].…”
Section: Trend Of Prevalence Of Self-reported Diabetic Retinopathy Inmentioning
confidence: 99%
“…Therefore, screening for DR should be done promptly after diagnosis and at regular risk-based intervals thereafter. Numerous factors are known to affect attendance at DR screening [87][88][89][90][91]. In an established mobile retinal screening service in Scotland, poor attendance at screening was not linked to gender or to distance from the event, but was associated with younger age, longer duration of diabetes, smoking, social deprivation, and poor HbA1c and blood pressure control; the highest proportion of non-attenders were in urban areas [92].…”
Section: Barriers To Screeningmentioning
confidence: 99%
“…Geographic information system (GIS) mapping is useful for visualizing geographic access and barriers to eye care and may help identify underserved areas that would benefit from expansion of teleophthalmology screening programs [88]. In North Carolina, the authors used data on 1787 patients with diabetes who underwent retinal screening to develop qualitative GIS maps of patient and provider density around five telemedicine sites [88]. Results indicated that patient accessibility to healthcare professionals can be limited by geography and road networks.…”
Section: Barriers To Screeningmentioning
confidence: 99%
See 1 more Smart Citation